PENGARUH KOMPENSASI, MOTIVASI, DAN GAYA KEPEMIMPINAN TERHADAP KEPUASAN KERJA ( Studi Pada Badan Kepegawaian Daerah Kota Semarang ) - Afrizal Dhida Raditya, 14.05.51.0056; Kasmari, Kasmari (Students' Journal of Economic and Management, 2018)
This study aims to examine and analyze the influence of compensation, motivation, and leadership style on job satisfaction in Badan Kepegawaian Daerah Kota Semarang. Respondents of this research consisted of 75 people Badan Kepegawaian Daerah Kota Semarang. Data analysis used is the test of validity, reliability test and multiple linear regression analysis using IBM SPSS software version 20.0 to test and prove the research hypothesis. The result of multiple linear regression test shows that Compensation has positive and not significant influence to job satisfaction, motivation has positive and significant influence to job satisfaction, leadership style has positive and significant influence to job satisfaction. Keywords: Compensation, Motivation, Leadership Style and Job Satisfaction